Perancangan Interior Pub dan Bar Di Semarang - Chandra, Angga Wijaya (Intra, 2015)
Pub & Bar business is a business that sells a comfortable atmosphere for relaxing and socializing Pub & Bar also often used as a place to hang out or socialize and entertain business associates, but pubs and bars in Indonesia canât be used to accommodate activities to facilitate business activity, with the concept of "Hamony in Diversity" pub and bar interior design is made in accordance with the theme and the needs of existing problems, not only to socialize but designed to facilitate business activity. Interior design applied in pubs and bars is based on the needs of the wearer so as to provide space to accommodate business events are made semi-private space.Â Â Â